An investigation into the sterilisation capabilities of biopolymers and the introduction of an organisational knowledge management methodology for the medical device industry - CHARLEY HAYNES (2022)
The medical device industry is currently under pressure to improve the sustainability of the products that are manufactured and used. Two single use medical device products manufactured from Acrylonitrile Butadiene Styrene (ABS) and PolyCarbonate were chosen to explore whether they could be replaced with biobased or biodegradable alternatives. Seven alternative polymers are selected as candidate materials based on their mechanical properties being desirable for these devices. The first objective of this research is to assess the magnitude of deterioration in mechanical properties of alternative polymers with two sterilisation methods, Gamma and Ethylene Oxide sterilisation. The polymers are pull tested and three-point bend tested to determine their tensile and compressive properties respectively. These tests are completed before sterilisation, after gamma irradiation, and after ethylene oxide sterilisation. The results show that a biodegradable polymer manufactured from starch-based Poly(Lactic Acid) PLA is as a viable option to replace ABS. The tests also concluded polymers with a higher fibre content experience a larger deterioration in properties after sterilisation, however a non-linear variation was in this relationship. Such results provide valuable organisational knowledge. Much of which is difficult to access, reuse and is lost over a period of time. This leads to the second objective of this research i.e. to evaluate the use of Failure Modes and Effects Analysis (FMEA) tables to store and reuse organisational knowledge required for root cause analysis. A bottom up approach is followed wherein business questions were gathered from employees of a medical device manufacturing company to determine the type of information that staff require access for root cause analysis. The data/information stored is either stored in an enterprise resource planning (ERP) system or the FMEA tables. A methodology is proposed that stores information in a graphical database using entity relationship diagrams that are analogous to the terminology used within the FMEA guideline documents. The FMEA data for an industrial partner for the two selected medical devices is populated in a prototype graph date base software. It is suggested that if the data is stored within a graphical database structure within the software, then this data pull can be automated allowing easy access and reuse. This also ensures that the knowledge is not lost over a period of time.